Larger body size leads to greater female beluga whale ovarian reproductive activity at the southern periphery of their range. Issue 23 (23rd November 2021) - Ferguson, Steven H.; Yurkowski, David J.; Hudson, Justine M.; Edkins, Tera; Willing, Cornelia; Watt, Cortney A.
Abstract: Identification of phenotypic characteristics in reproductively successful individuals provides important insights into the evolutionary processes that cause range shifts due to environmental change. Female beluga whales ( Delphinapterus leucas ) from the Baffin Bay region (BB) of the Canadian Arctic in the core area of the species' geographic range have larger body size than their conspecifics at the southern range periphery in Hudson Bay (HB). We investigated the mechanism for this north and south divergence as it relates to ovarian reproductive activity (ORA = total corpora) that combines morphometric data with ovarian corpora counted from female reproductive tracts. Our study aim was to assess the relative influence of age and body size of female beluga whale on ORA in the two populations. Female beluga whale ORA increased more quickly with age (63% partial variation explained) in BB than in HB (41%). In contrast, body length in HB female beluga whales accounted for considerably more of the total variation (12% vs. 1%) in ORA compared to BB whales. We speculate that female HB beluga whale ORA was more strongly linked with body length due to higher population density resulting in food competition that favors the energetic advantages of larger body size during seasonal food limitations. Understanding the evolutionary mechanism of how ORA varies across a species' range will assist conservation efforts in anticipating and mitigating future challenges associated with a warming planet. Abstract : Beluga whales in the eastern Canadian Arctic group into a core region in the north and a peripheral region in the south composed of smaller whales. We test for the relative contribution of size while controlling for age and find that the peripheral beluga whale body length is more strongly linked to ovarian reproductive activity (total corpora) than the core whales. We consider the ecological and evolutionary explanations for this difference and how it may relate to shifts in geographic range with warming.